2020
DOI: 10.1097/md.0000000000022837
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thrower's Ten exercises on upper extremity performance

Abstract: Objectives: The Thrower's Ten Exercise program is an exercise program especially designed to improve the strength, power and endurance of the shoulder complex. The aim of this study was to investigate the effects of the Thrower's Ten exercises on the upper extremity performance in healthy sedentary individuals. Methods: 36 healthy sedentary individuals completed this study conducted with a randomized controlled design. The subjects were divided into 2 groups: exercise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It was inferred that the thrower's specific warm-up program improved the stability of the upper limb. An RCT done by Gokalp in 2020 concluded that 8 weeks of thrower's ten exercises improves upper limb balance (assessed using the Upper Limb Y-balance test) in healthy people with a sedentary lifestyle [16]. This program includes movement patterns, including throwing-specific motions, high-level neuromuscular control, endurance, dynamic stabilization, coordination, and force [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was inferred that the thrower's specific warm-up program improved the stability of the upper limb. An RCT done by Gokalp in 2020 concluded that 8 weeks of thrower's ten exercises improves upper limb balance (assessed using the Upper Limb Y-balance test) in healthy people with a sedentary lifestyle [16]. This program includes movement patterns, including throwing-specific motions, high-level neuromuscular control, endurance, dynamic stabilization, coordination, and force [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Four throwing trials were carried out, and their mean distance was noted for further analysis [20,32,33]. Thrower's ten protocol includes 17 exercises that specifically focus on training the upper limb in throwers [11,[13][14][15][16]22]. The 17 exercises are: 1adiagonal pattern D2 flexion, 1b-diagonal pattern D2 extension, 2a-ER at 0° abduction, 2b-IR at 0° abduction, 2c-ER at 90° abduction, 2d-IR at 90° abduction, 3-shoulder at 90° abduction, 4-scaption IR, 5a-prone horizontal abduction (neutral), 5b-prone horizontal abduction (full ER), 6-seated press-ups, 7-prone rowing, 8-push-ups, 9a-elbow flexion, 9b-elbow extension, 10a-wrist flexion, 10b-wrist extension, 10c-supination, 10dpronation [25,[37][38][39] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation